Psychosocial variables as prospective predictors of violent events among adolescents. - Sussman S; Dent CW; Stacy AW; Burton D; Flay BR (Health Values: The Journal of Health Behavior, Education & Promotion)
Violent events are main causes of mortality among children and include intentional (e.g., homicide) and unintentional (e.g., accidents) circumstances. This study investigated the prediction of the self-reported occurrence of 14 violent events among eighth-grade youth from psychosocial variables measured in these same youth in seventh grade. Psychosocial variables included tobacco and alcohol use, demographic variables, interpersonal variables such as family conflict, and intrapersonal variables such as risk taking. An iterative procedure, involving selection of a set of predictors and a test of the correlation of the set of predictors to the set of events, provided support for an extension of problem behavior theory to violent events.